Metrology in Chemistry - Bulska, Ewa (Lecture Notes in Chemistry,, 2018)
In this concise book, the author presents the essentials every chemist needs to know about how to obtain reliable measurement results. Starting with the basics of metrology and the metrological infrastructure, all relevant topics - such as traceability, calibration, chemical reference materials, validation and uncertainty - are covered. In addition, key aspects of laboratory management, including quality management, inter-laboratory comparisons, proficiency testing, and accreditation, are addressed. .